Pendampingan Tata Laksana Surat oleh Sekretaris Lingkungan di Paroki Salib Suci Tropodo Keuskupan Surabaya - Hadisoebroto, Andreas Emmanuel; Lestari, Indriana; Adven Sarbani, Yohanes; Nelladia Cendra, Anastasia; Suryo Subandoro, Philipus (ISAS (Indonesian Society of Applied Science), 2022)
The community service activities “Administration Assistance for the Church Regional Secretaries at Paroki Salib Suci Tropodo” was carried out to answer the expectations of the Surabaya Diocese for uniformity in handling administrative, especially in the use of letter heads, and making letters, and forms. The method of implementing community service activities was carried out in several stages, namely: First, conducting discussions with the Head of the Surabaya Diocese Pastoral Center to synchronize the perceptions and to consult on letter guidelines that will be used by the Church Regional Secretaries. Second, conducting discussions and interviews with the Church Regional Secretaries at Paroki Salib Suci Tropodo. Third, providing briefing on the use of letterheads and form templates for the Church Regional Secretaries at Paroki Salib Suci Tropodo